2016
DOI: 10.1111/iwj.12671
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma complicating a chronic lesion of hidradenitis suppurativa: a case report and review of the literature

Abstract: Squamous cell carcinoma (SCC) arising from chronic hidradenitis suppurativa (HS) is rare; however, the morbidity associated with this presentation is high and management has not been standardised or optimised. We present a case of HS of the perineum and buttocks complicated by SCC, requiring multiple extensive surgical resections. Adjuvant radiotherapy was withheld initially because of concern for poor healing of the surgical wound but was eventually initiated after a second recurrence was identified. The pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(87 citation statements)
references
References 16 publications
(27 reference statements)
1
67
1
3
Order By: Relevance
“…One of the most serious complications of long‐term HS is the development of aggressive, metastatic squamous cell carcinoma . Despite their well‐differentiated nature, these tumours rapidly metastasize and can be fatal.…”
Section: Stromal Cell Contribution May Explain Aggressive Behaviour Omentioning
confidence: 99%
“…One of the most serious complications of long‐term HS is the development of aggressive, metastatic squamous cell carcinoma . Despite their well‐differentiated nature, these tumours rapidly metastasize and can be fatal.…”
Section: Stromal Cell Contribution May Explain Aggressive Behaviour Omentioning
confidence: 99%
“…Although rare, the development of squamous cell carcinoma (SCC) superimposed on chronic HS has a high morbidity. Studies have shown that long-lasting HS and the involvement of the buttocks and perineal areas increase the risk of malignant transformation to SCC (6,7). When SCC does arise in HS it is usually well differentiated; however, despite the theoretical good prognosis, the combination of SCC and HS is often associated with early metastasis and high mortality rates (8).…”
Section: Introductionmentioning
confidence: 99%
“…A paper in 2016 by Jourabchi et al and in 2018 by Chapman et al described 80 and five cases, respectively, on SCC in patients with HS cases in the English literature. We found five additional cases of SCC arising from HS reported in the literature since the last updated review by Chapman et al (Table ).…”
Section: Case Reportmentioning
confidence: 99%